Role of Gender and Genetic Variance in Plasminogen Activator Inhibitor-1 Secretion from Human Adipose Tissue - Van Harmelen, Vanessa; Wahrenberg, Hans; Eriksson, Per; Arner, Peter (Thrombosis and Haemostasis, 2000)
Gender and the 4G/5G polymorphism in the plasminogen activator inhibitor 1 (PAI-1) gene are believed to play a role in the regulation of plasma PAI-1 activity. Adipose tissue has been found to be an important source of PAI-1. The possible influence of gender and the 4G/5G polymorphism in the PAI-1 gene on PAI-1 secretion from abdominal subcutaneous adipose tissue was investigated in 59 women and 32 men. The subjects were apparantly healthy, although they differed markedly inter-individually in body mass index (21-53 kg/m2). The 4G/5G polymorphism did not influence the adipose secretion rate of PAI-1 or plasma PAI-1 activity. There was no gender difference in the adipose secretion of PAI-1. In multiple regression, including body mass index (BMI), waist-to-hip ratio (WHR), plasma insulin and plasma triglycerides as the independent and adipose PAI-1 secretion as the dependent variable, only BMI and plasma triglycerides correlated independently with adipose PAI-1 secretion (r = 0.54, p <0.05; r = 0.51, p <0.05, respectively). Men had a two times higher plasma PAI-1 activity than women (p <0.05). This gender difference was mainly due to gender differences in WHR. In multiple regression analysis, BMI and WHR were identified to be independently correlated with plasma PAI-1 activity (r = 0.60, p <0.05; r = 0.52, p = 0.01, respectively). In conclusion, neither gender nor the 4G/5G polymorphism in the PAI-1 gene are associated with secretion of PAI-1 from abdominal subcutaneous adipose tissue.